Answer:
C. 3
Explanation:
First I'll solve y + 1 = 3x - 12 for y.
y + 1 = 3x - 12 All you need to do for this first part is subtract 1 from both sides.
y = 3x - 12 - 1
y = 3x - 13
I'll use the point for x being 6, and x being 12.
3(6) - 13
18 - 13
5
y is 5 when x is 6. (6, 5)
3(12) - 13
36 - 12
y is 23 when x is 12. (12, 23)
The formula for slope is y2-y1/x2-x1
(23 - 5)/(12 - 6) Subtract 5 from 13, and then subtract 6 from 12.
18/6 Divide 18 by 6.
3
The slope to the line y + 1 = 3(x - 4) is 3, which is C.